The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1017/s1481803500013312
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes of pediatric patients transported by emergency medical services in a Canadian prehospital system

Abstract: Objectives: There is uncertainty around the types of interventions that are provided by emergency medical services (EMS) to children during prehospital transport. We describe the patient characteristics, events, interventions provided and outcomes of a cohort of children transported by EMS. Methods: This prospective cohort study was conducted in a city of 750 000 people with a 2-tiered EMS system. All children <16 years of age who were attended by EMS during a 6-month period were enrolled. Data were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
48
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 24 publications
(26 reference statements)
12
48
0
4
Order By: Relevance
“…Similar rates were reported by Nagele et al [6] in Austrian ground-based EMS, whereas a higher frequency was found in European HEMS [2,4,13,14]. In contrast, previous studies from US/ Canadian EMS showed that the frequency of tracheal intubation as well as CPR by paramedics is lower than 1% in pediatric emergencies [10,21,22]. Our average rate of pediatric tracheal intubation performed by individual HEMS emergency physician was in line with the literature, clearly indicating that some teams go without a pediatric airway in several years [23,24].…”
Section: Discussionsupporting
confidence: 78%
“…Similar rates were reported by Nagele et al [6] in Austrian ground-based EMS, whereas a higher frequency was found in European HEMS [2,4,13,14]. In contrast, previous studies from US/ Canadian EMS showed that the frequency of tracheal intubation as well as CPR by paramedics is lower than 1% in pediatric emergencies [10,21,22]. Our average rate of pediatric tracheal intubation performed by individual HEMS emergency physician was in line with the literature, clearly indicating that some teams go without a pediatric airway in several years [23,24].…”
Section: Discussionsupporting
confidence: 78%
“…12 The distribution of patient ages was assumed to be equal among the nine weighted categories, based on an examination of previously published data. 13 In the numerical simulations, we assumed varying rates of disagreement between the two assessments, ranging from 0% to 50% disagreement. Under each assumed rate of disagreement, we simulated 1,000 trials, each with simulated patients, and calculated the resulting unweighted kappa coefficient that would be obtained.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…In these seizure calls, EMS providers checked the patient's blood glucose by glucometry 70% of the time. 35 A study by Kumar showed that capillary blood glucose values measured by glucometer best approximate venous blood glucose values from the laboratory and can be used effectively to guide clinical decisions in the field. 36 A review article on pediatric seizures by Friedman recommends rapid, point of care glucometry in all actively seizing pediatric patients.…”
Section: Glucometrymentioning
confidence: 99%